MANAJEMEN DAN BUDAYA PERPUSTAKAAN BUDAYA KERJA STAFF PENGADAAN PERPUSTAKAAN UNIVERSITAS INDONESIA - Zahra Zalmi, Fathonah (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
Culture is essential for an organization, because it will always relate to the life that exists in the organization. Organizational culture is a philosophy, ideology, values, assumptions, beliefs, expectations, attitudes and norms that are shared and binding in a particular community. Specifically, the culture in the organization will be determined by the working conditions of the team, leadership and organizational characteristics as well as the prevailing administrative processes (Koesmono, 2005). Organizational culture is important, because it is the habits that occur in the organizational hierarchy that represent the behavioral norms followed by members of the organization. A productive culture is a culture that can make the organization strong and the goals of the organization can be accommodated. In the organization, of course, many factors influence a person to achieve the goals that have been set, while the course of the organization is certainly colored by the behavior of individuals who feel interested in their respective groups. The behavior of individuals who are in the organization certainly greatly affects the organization both directly and indirectly, this is due to the different abilities of individuals in dealing with their tasks or activities. Every human being or a person always considers his behavior towards everything that is desired so that it can be achieved without causing conflict, both individually and in groups, so that performance can be achieved as desired. This can be used as an indication that the library is an organization so organizational theories can be applied in the library. The library as part of the parent institution, develops in line with the development of the library, which will appear in the components of collections, services, buildings/spaces and equipment and personnel. The purpose of the library can be achieved through good management and is an interaction between individuals who are in it.